2019
DOI: 10.1155/2019/9097876
|View full text |Cite
|
Sign up to set email alerts
|

Lumbopelvic Fixation for Sacral Insufficiency Fracture Presenting with Sphincter Dysfunction

Abstract: Sacral insufficiency fractures (SIFs) are common in the elderly. In patients with SIF, objective neurological abnormalities such as sphincter dysfunction or leg paresthesia are uncommon. We present a case of SIF accompanied by spinopelvic dissociation with late neurological compromise treated by spinopelvic fixation. A 61-year-old woman presented to our hospital with low back pain without obvious trauma history. She had a past history of eosinophilic granulomatosis with polyangiitis and treatment with steroids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
(19 reference statements)
0
13
0
1
Order By: Relevance
“…Schmitz et al showed for the cement-augmented screw-rod system good postoperative mobility in 10 out of 15 patients but had surgical complications in 5 out 15 patients [ 11 ]. For lumbopelvic fixation, there is only one case report reporting good clinical outcome [ 12 ] and compared to the other techniques it is more invasive. Percutaneous screw stabilization is often used for osteoporotic fractures, because they can be implanted minimally invasive and ensure early mobilisation at low perioperative risk.…”
Section: Background/introductionmentioning
confidence: 99%
“…Schmitz et al showed for the cement-augmented screw-rod system good postoperative mobility in 10 out of 15 patients but had surgical complications in 5 out 15 patients [ 11 ]. For lumbopelvic fixation, there is only one case report reporting good clinical outcome [ 12 ] and compared to the other techniques it is more invasive. Percutaneous screw stabilization is often used for osteoporotic fractures, because they can be implanted minimally invasive and ensure early mobilisation at low perioperative risk.…”
Section: Background/introductionmentioning
confidence: 99%
“…Considering this as a form of unstable spinopelvic dissociation, the authors performed L3 to S1 lumbopelvic fixation. The patient had full recovery at 6 months [13]. Attempts to classify SIF and guide management according to classification have been recently made [2,17].…”
Section: Discussionmentioning
confidence: 99%
“…Neurological involvement in SIF is rare, with an incidence of 2.8% reported [6,7]. Objective signs of neurological involvement may include sphincter disturbance, motor weakness, or leg paraesthesia [13]. While conservative management of SIF generally has satisfactory outcomes, management in the setting of neurological involvement and coexisting spinal pathology—particularly in elderly patients—is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…iliosacral screw fixation ((iss) is a commonly used treatment method, but some studies have shown that through this method satisfactory mechanical stability is not achieved, which leads to displacement and instability of the screws (39). lumbosacral fixation technique is indicated in patients with neurological complications due to unstable sacral fractures (40).…”
Section: Discussionmentioning
confidence: 99%
“…iliosakralna fiksacija vijcima često je upotrebljavana metoda liječenja, no neka su istraživanja pokazala da se ovom metodom ne postiže zadovoljavajuća mehanička stabilnost, što dovodi do pomicanja i nestabilnosti vijaka (39). lum bosakralna fiksacija indicirana je u bolesnika s neurološkim komplikacijama zbog nestabilnog prijeloma sakruma (40).…”
Section: Discussionunclassified